De-escalating rituximab dose results in stability of clinical, radiological, and serum neurofilament levels in multiple sclerosis. (July 2021) - Disanto, Giulio; Ripellino, Paolo; Riccitelli, Gianna C; Sacco, Rosaria; Scotti, Barbara; Fucili, Anita; Pravatà, Emanuele; Kuhle, Jens; Gobbi, Claudio; Zecca, Chiara
Background: Phase II and observational studies support the use of rituximab in multiple sclerosis. Standard protocols are lacking, but studies suggest comparable efficacy between low- and high-dose regimens. Objective: To evaluate effectiveness and safety of de-escalating rituximab dose from 1000 to 500 mg/6 months in multiple sclerosis. Methods: Patients were switched from rituximab 1000 to 500 mg/6 months and prospectively followed for 12 months. Relapses, disability, occurrence of brain/spinal magnetic resonance imaging (MRI) lesions, serum neurofilament light chain (NfL), CD19 +  B cell, and IgG concentrations were analyzed. Results: Fifty-nine patients were included (37 relapsing-remitting, 22 secondary progressive). No relapses occurred, with no difference in expanded disability status scale (EDSS) between baseline (4 (2.5–4.5) and 12 months (3.5 (2.5–5.5) p  = 0.284). Overall, three new T2 lesions appeared during follow-up. NfL concentration was stable between baseline (7.9 (5.9–45.2) pg/mL) and 12 months (9.1 (5.9–21.3) pg/mL, p  = 0.120). IgG concentrations decreased with greater rituximab load (coefficient = −0.439, p  = 0.041). IgG deficient patients had greater risk of infections (OR = 6.27, 95% CI = 1.71–22.9, p  = 0.005). Conclusion: De-escalating rituximab dose from 1000 to 500 mg/6 months is safe, results in clinical and radiological stability, and does not affect serum NfL over 12 months. Rituximab load negatively influences IgG concentrations, and IgG deficient patients are at higher risk of infections.